'Cine-Gwangju': envisioning the Gwangju uprising in South Korean film and culture. Issue 1 (2nd January 2022) - Park, Hyun Seon
ABSTRACT: This is an introduction to a special section of 'Cine-Gwangju' that consists of four essays.